Classic Literature and Millennial Consumers: Branding Challenges for Balai Pustaka - Sutianingsih (Jobmark: Journal of Branding and Marketing Communication, 2023)
Balai Pustaka's literacy branding strategy aims to foster Indonesian millennial’s reading interest in old classic literary works by carrying out various strategies ranging from brand awareness strategies, brand knowledge strategies, brand image strategies, brand experience strategies, brand loyalty strategies, and brand spirituality strategies. Using a descriptive case study method, this study found various literacy branding strategies for classic literary works carried out by Balai Pustaka, such as the existence of republish programs, adaptations, and TBM (community reading gardens) to media conversion through filmmaking. This research is helpful as a reference for researchers in literacy branding, which still needs to be explored.